Trauma-informed human rights teaching in higher education - Louise Loder (Journal of Learning Development in Higher Education)
In higher education environments, there is a high probability that some learners will have lived experience of conflict, violence, terrorism, forced exile, climate-related natural disasters and other significant human rights events. Human rights education (HRE) typically engages learners with these and many other complex and emotionally challenging topics. Educators are generally aware of the risk that engaging with these topics in the human rights curriculum may elicit trauma responses from learners, but they may not be as acutely aware of the risks of vicarious or secondary trauma to both learners and educators from such engagement, or of how trauma-informed teaching practice can help to mitigate those risks. This article examines pedagogical approaches that can guide educators through creative, conscious adoption of trauma-informed practice in their human rights teaching. These approaches invite educators to undergo a process of clarifying their own values and articulating their teaching personas, align content design with trauma-informed principles and the UN’s ‘learning about, through and for’ framework for holistic human rights education, and embed opportunities in session design for dialogic engagement and structured reflection as a tool for self-understanding, self-empathy and resilience building.